2006
DOI: 10.1089/end.2006.20.717
|View full text |Cite
|
Sign up to set email alerts
|

Third Prize: Randomized Trial of Laparoscopic Donor Nephrectomy with and without Hand Assistance

Abstract: Laparoscopic and hand-assisted donor nephrectomies have similar outcomes and postoperative pain. Both approaches are well tolerated with minimal complication rates and have similar impact on patients' quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(36 citation statements)
references
References 16 publications
1
35
0
Order By: Relevance
“…The most important arguments for using hand assistance concerned reduction of the operating time, warm ischemia time, and increased safety and control. These arguments confirm that hand-assisted LDN is not only used during the learning phase of LDN but has also become a true alternative with similar outcomes (20). Our results confirm this because there was no relation between the use of hand assistance and years of experience or case volume.…”
Section: Discussionsupporting
confidence: 81%
“…The most important arguments for using hand assistance concerned reduction of the operating time, warm ischemia time, and increased safety and control. These arguments confirm that hand-assisted LDN is not only used during the learning phase of LDN but has also become a true alternative with similar outcomes (20). Our results confirm this because there was no relation between the use of hand assistance and years of experience or case volume.…”
Section: Discussionsupporting
confidence: 81%
“…10 Dividing their study into two halves, the group found that operative times decreased from 293 to 232 More recently, Bargman et al analysed 40 donor nephrectomies in a randomised control study, involving equal numbers undergoing lN and Hal. 13 With mean operative times of 200 and 219 minutes (p=0.02) for lN and Hal respectively, they demonstrated that lN can be quicker than Hal. Furthermore, there are reports of an increase in complications when using Hal, with a risk of wound complications.…”
Section: Discussionmentioning
confidence: 95%
“…This has been already reported in many studies including hands. 9,10 All the 16 kidneys harvested by laparoscopic method were transplanted successfully in the recipients with only 2 (12%) conversion to open due to bleeding from posterior lumbar vein where bleeding was controlled, but we found difficulty in repairing it laparoscopically. Conversion rate in SGPGI is 10.1%.…”
Section: Methodsmentioning
confidence: 92%
“…We have compared our study with similar studies, where multiple factors were analysed for outcome of donors following laparoscopy and the graft function in recipients. 1,6,7,8,9 In our series, we have selected only a left side kidney for laparoscopic procedure which is easier technically because of long renal vein on left side. This has been already reported in many studies including hands.…”
Section: Methodsmentioning
confidence: 99%